COMPARING THE EFFICACY OF 30 ML AND 60 ML FOLEY’S CATHETER BALLOON INFLATION FOR INDUCTION OF LABOR IN TERM SINGLETON MULTIGRAVIDA PATIENTS: A RANDOMIZED TRIAL - SHAHZADI , A (Biological and Clinical Sciences Research Journal, 2024)
Labour induction is a common obstetric technique, especially for term singleton multigravida patients. The Foley’s catheter balloon inflation method is widely used, and the efficacy of this technique may be affected by differences in balloon capacity. Thus, this study aimed to compare the effectiveness of two balloon inflation volumes, 30 mL and 60 mL, for inducing labour in term singleton multigravida patients. This study was a prospective, randomized, parallel-group design conducted at Gajju Khan Medical College, Swabi, between September 2022 and September 2023 The study included 112-term singleton multigravida with a gestational age of 37 weeks or more, a single-fetus pregnancy, and prior pregnancies. Using computer-generated random numbers, participants were randomly assigned to Group A (30 mL) or Group B (60 mL). The results of the study showed that both groups had similar baseline characteristics. Group A had an average age of 28.5 years, while Group B had an average age of 29.2 years. Group A’s mean gestational age was 39.1 weeks, while Group B’s was 38.9 weeks. Patients in both groups were multiparous. The mean induction-to-delivery delay was 10.2 days for Group A and 12.8 days for Group B, with a statistically significant difference (p=0.034). After balloon inflation, Group A bishop scores improved from 4.2 to 7.8, and Group B bishop scores improved from 4.1 to 7.6 (p=0.498). The research shows that 60 mL of folleys catheter balloon inflation for cervical ripening in labour induction may shorten the induction-to-delivery period without compromising newborn outcomes.